Sistem Informasi Kuliah Kerja Nyata (KKN) Dengan Metode Pigeon Hole Untuk Menentukan dan Mengelompokkan Peserta KKN - Aristoteles .; Rico Andrian; Agatha Beny Himawan (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
This research is conduct to make a system called â€œInformation System of KKN with Pigeon Hole Method for Determine and Grouping KKN Participantâ€. Grouping KKN participant based on gender and major of faculty. Grouping KKN participant based on gender is every KKN group consist of 7 participant that consist of 3 male and 4 female. Grouping KKN participant based on majority and faculty is every KKN group consist of 7 participant that consist max 2 participant from same major and max 3 participant from same faculty. The result of grouping KKN participants based on each assumptions is percentage of system accuracy in classifying participant KKN is not much different from the ideal of percentage each group data. This information system of KKN is make using prototype method which is part of SDLC. Information system of KKN can be use as a means by students to participate KKN process. Information system of KKN with pigeon hole method make placement and grouping KKN participant more easy and well ordered.Keywords: KKN, Pigeon Hole, Prototype, System Development Life Cycle